Behavior of load‐bearing glass at elevated temperature. Issue 5 (22nd October 2018) - Honfi, Dániel; Lange, David; Kozłowski, Marcin; Sjöström, Johan; Lenk, Peter
ABSTRACT: The use of glass as a structural material has increased in the built environment over the last decades. Despite the large number of research projects and studies, it still poses difficulties in structural design. This particularly applies to the behaviour of glass in fire and under elevated temperatures since the available data on temperature dependent mechanical and thermal properties of glass is still limited. This contribution provides a brief overview of material properties of glass at elevated temperature and elaborates on current requirements for the fire safety included in standards.